Controlling the dipole blockade and ionization rate of Rydberg atoms in strong electric fields - Stecker, Markus; Nold, Raphael; Lea-Marina Steinert; Grimmel, Jens; Petrosyan, David; tágh, József; Günther, Andreas (arXiv.org, 2019)
We study a novel regime of the Rydberg excitation blockade using highly Stark-shifted, yet long-living, states of Rb atoms subject to electric fields above the classical ionization limit. Such states allow tuning the dipole-dipole interaction strength while their ionization rate can be changed over two orders of magnitude by small variations of the electric field. We demonstrate laser excitation of the interacting Rydberg states followed by their detection using controlled ionization and magnified imaging with high spatial and temporal resolution. Our work reveals the hitherto unexplored possibilities to control the interaction strength and dynamically tune the ionization and detection of Rydberg atoms, which can be useful for realizing and assessing quantum simulators that vary in space and time.